Well-being and life satisfaction in Argentinean adolescents - Gongora, Vanesa Carina (2014)
Seligman proposes that well-being can be achieved by three main pathways: thepleasant life or positive emotions, the engaged life, and the meaningful life. The aimsof this study are to investigate the three pathways to well-being in Argentineanadolescents and analyze their relationship to life satisfaction. A sample of 255Argentinean adolescent students (110 boys and 145 girls) who were between 13 and 18years of age was used in this study. Participants completed the Three Pathways to Well-being Scale and the Satisfaction with Life Scale. Argentinean adolescents scoredhighest in the pleasant life, second highest on the engaged life and lowest on themeaningful life. The results showed that among the three pathways, only the engagedlife was a significant predictor of life satisfaction; however, this was found only in asmall proportion of variance (8%). In consonance with well-being theory, thoseadolescents who can make use of the three pathways at a high level reported thehighest level of life satisfaction. Results were similar to previous findings in adultpopulation.